2005
DOI: 10.1016/j.febslet.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ/IRF‐1‐induced p27kip1 down‐regulates telomerase activity and human telomerase reverse transcriptase expression in human cervical cancer

Abstract: Telomerase activation is regulated by the expression of human telomerase reverse transcriptase (hTERT) and is a key step in the development of human cancers. Interferon-c (IFN-c) signaling induces growth arrest in many tumors through multiple regulatory mechanisms. The p27 tumor suppressor protein inhibits the formation of tumors through the induction of cell cycle arrest and/or apoptosis. We demonstrate here that p27 Kip1 inhibits hTERT mRNA expression and telomerase activity through post-transcriptional up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…IFNg inhibits cell proliferation via cell type-specific pathways that involve CKIs, such as p21Cip1 (29,30) and p27Kip1 (31,32). It has been shown that STAT1 interacts directly with cyclin D1/ Cdk4 and mediates the cell-cycle arrest of human U3A cells (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFNg inhibits cell proliferation via cell type-specific pathways that involve CKIs, such as p21Cip1 (29,30) and p27Kip1 (31,32). It has been shown that STAT1 interacts directly with cyclin D1/ Cdk4 and mediates the cell-cycle arrest of human U3A cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Mice transgenic for the pmel-1-TCR, which recognizes the H-2D b -restricted epitope EGSRNQDWL from gp100 (gp100 [25][26][27][28][29][30][31][32][33] ), were obtained from The Jackson Laboratory. All mice were housed in a pathogen-free environment, and all animal procedures were conducted in accordance with institutional guidelines.…”
Section: Mice Tumor Cells and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ may directly or indirectly affect apoptosis of some cancer cells (Wagner et al, 1997;Tu et al, 2011;Ni et al, 2013), such as glioma cells (Rajiv et al, 2008), multiple myeloma cells and cervical cancer cells (Lee et al, 2005;Lindkvist et al, 2006). It can also induce aging of human endothelial cells, thus leading to cell cycle change (Kim et al, 2009), and 1 * affect the expression of genes such as Secretoglobin 3A1 (SCGB3A1) (Yamada et al, 2009), osteopontin (OPN) (Xinfang et al, 2003), CXCR3 binding chemokine IP-10 (CXCL10) (Yeruva et al, 2008), and the phosphorylation of signal transducer and activator of transcription (STAT1), for example (Mitchell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mice de cient in p27 exhibit increased susceptibility to tumor progression, and tumorigenecity is accelerated in Rb +/-p27 -/-and p18INK4c -/-p27 -/-mice [22], suggesting that p27 Kip1 is a rate-limiting factor for tumorigenesis. Lee et al found the direct evidence related to the e ect of p27 on hTERT expression in both human CC cells and primary MEFs de cient in p27 [23]. In the present study, the HeLa and SiHa cells were independently transfected with miR-222 to interfere with the miR-222 expression.…”
Section: Discussionmentioning
confidence: 96%